Virtual bronchoscopic navigation and guided radial endobronchial ultrasound for peripheral pulmonary lesions: harmonizing modalities to optimize accuracy - Parul Mrigpuri; Sidharth Raj Yadav; Divyendu Sharma; Sonam Spalgais; Vidushi Rathi; Nitin Goel; Balakrishnan Menon; Raj Kumar (Monaldi Archives for Chest Disease)
Peripheral pulmonary lesions (PPLs) present a significant diagnostic challenge due to their location beyond the reach of traditional bronchoscopy. With lung cancer being the leading cause of cancer-related mortality worldwide, accurate and early diagnosis of PPLs is crucial. Virtual bronchoscopic navigation (VBN) combined with radial endobronchial ultrasound (R-EBUS) has emerged as a promising technique to enhance the diagnostic yield for these lesions. This retrospective observational study evaluated the diagnostic yield of VBN-guided R-EBUS in patients with PPLs identified on computed tomography. The study included nine patients who underwent VBN-guided R-EBUS biopsy sampling. Patient demographics, lesion characteristics, and procedural outcomes were analyzed using descriptive and inferential statistics. The mean age of the patients was 57.33 years, with a mean lesion size of 3.24 cm. The diagnostic yield of VBN-guided R-EBUS was 77.7% (95% confidence interval: 68.5-85.8%). Non-small cell carcinoma was the most frequent histopathological diagnosis (55.5%). Complications included bleeding in two patients (22.2%) and bronchospasm in one patient (11.1%), all managed conservatively. VBN-guided R-EBUS provides high diagnostic accuracy and a low risk of complications in patients with PPLs.